Portal vein thrombosis as a thrombotic complication of COVID-19 mRNA vaccine: A case report and literature review. (2022) - Shrestha, Prakriti Singh; Ishak, Angela; Napit, Arun R.; Sarwar, Sarosh; Rai, Niraj; Nizami, Zoha; Bheemisetty, Niharika; Jayaraj, Prashanth; Shrestha, Amardeep; Rodriguez, Ivan D.
Abstract: Thrombosis following COVID-19 vaccination commonly occurs with vector-based vaccines. The proposed mechanism is vaccine-induced thrombotic thrombocytopenia (VITT), with thrombocytopenia as principal manifestation. We present a 51-year-old male who came with isolated portal vein thrombosis (PVT) one day after Moderna vaccination, without associated thrombocytopenia, challenging VITT as being the only patho-mechanism. Further exploration of these possible alternative mechanisms is needed for COVID-19 vaccine-related thrombotic complications.